2017
DOI: 10.1007/s00223-017-0381-1
|View full text |Cite
|
Sign up to set email alerts
|

Bone Geometry, Quality, and Bone Markers in Children with Type 1 Diabetes Mellitus

Abstract: Adults with Type 1 diabetes mellitus show a high risk of bone fracture, probably as a consequence of a decreased bone mass and microarchitectural bone alterations. The aim of the study was to investigate the potential negative effects of type 1 diabetes on bone geometry, quality, and bone markers in a group of children and adolescents. 96 children, mean age 10.5 ± 3.1 years, agreed to participate to the study. Bone geometry was evaluated on digitalized X-rays at the level of the 2nd metacarpal bone. The follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
1
8

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 37 publications
2
18
1
8
Order By: Relevance
“…Our patients with T1DM showed reduced levels of 25(OH)D compared with the healthy controls. Consistently, in other studies it has been reported that patients with T1DM displayed vitamin D deficiency [ 11 , 20 , 28 , 47 , 54 , 59 ], and that insulin gene expression in pancreatic β -cells may also be modulated by vitamin D [ 20 , 35 , 37 , 76 ]. Vitamin D also modulates muscle and bone-derived hormones, hormones, including GH-IGF-1 axis and sex hormones, facilitating cross-talk between these tissues [ 77 ].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our patients with T1DM showed reduced levels of 25(OH)D compared with the healthy controls. Consistently, in other studies it has been reported that patients with T1DM displayed vitamin D deficiency [ 11 , 20 , 28 , 47 , 54 , 59 ], and that insulin gene expression in pancreatic β -cells may also be modulated by vitamin D [ 20 , 35 , 37 , 76 ]. Vitamin D also modulates muscle and bone-derived hormones, hormones, including GH-IGF-1 axis and sex hormones, facilitating cross-talk between these tissues [ 77 ].…”
Section: Discussionsupporting
confidence: 83%
“…Our results also demonstrate reduced BMC or BMD Z-scores and an impairment of the relationship between the fat and muscle tissue. Several previous studies also investigated this association and found similar results [ 16 18 , 20 , 21 , 29 , 44 46 , 58 , 59 ]. Our observations of reduced relative bone strength of T1DM patients, and more so in the poor metabolic control patients, have led us to speculate that maintaining such status may be associated with increased risk of fractures later in life.…”
Section: Discussionsupporting
confidence: 63%
“…In the end, 26 studies matched our criteria and were included; 20 cross‐sectional studies and six prospective cohort studies . One cohort by Saggese et al was an intervention cohort study, but since we did not use postintervention data, baseline data were used in the pooled meta‐analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies did not include control groups . Most studies made it clear that the included participants and controls had no concurrent diseases, and only two articles did not state this . Seven studies did not state whether the blood tests were drawn in a fasting state and only six studies reported on blood glucose levels when tested, ranging from 9.3 to 16.52 mmol/L …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation